2017
DOI: 10.1247/csf.16016
|View full text |Cite
|
Sign up to set email alerts
|

A FRET Biosensor for ROCK Based on a Consensus Substrate Sequence Identified by KISS Technology

Abstract: ABSTRACT. Genetically-encoded biosensors based on Förster/fluorescence resonance energy transfer (FRET) are versatile tools for studying the spatio-temporal regulation of signaling molecules within not only the cells but also tissues. Perhaps the hardest task in the development of a FRET biosensor for protein kinases is to identify the kinase-specific substrate peptide to be used in the FRET biosensor. To solve this problem, we took advantage of kinase-interacting substrate screening (KISS) technology, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Therefore, to examine this with more detail we evaluated whether or not rotenone‐induced RhoA activation involves an increase in ROCK activity using the Eevee‐ROCK biosensor (Li et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, to examine this with more detail we evaluated whether or not rotenone‐induced RhoA activation involves an increase in ROCK activity using the Eevee‐ROCK biosensor (Li et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…) and the Eevee‐ROCK was a kind gift of Dr. Matsuda (Li et al . ). Both constructs are unimolecular forster resonance energy transfer (FRET)‐based biosensor, which consists of genetically encoded fusions of a sensing module flanked with a donor fluorophore [a cyan fluorescent protein (CFP)] and an acceptor fluorophore (a yellow fluorescent protein) that allow ratiometric measurements (Fritz et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Abe et al previously compared the distribution of the membrane markers lyn-EGFP, EGFP-KRas, GAP43-EGFP, Display-Venus, and Display-mCherry, and concluded that lyn-EGFP performed best . We previously compared the ROCK biosensor tagged with the myristoylation signal of lyn, the KRas CAAX domain, and the HRas CAAX domain and found that the KRas CAAX domain worked best (Li et al, 2017). We need to further explore the best membrane marker for the in vivo imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the FLIM-FRET with a non-fluorescent protein enables multi-plexed imaging of molecular activity (Laviv et al, 2016). While one of the remaining difficulties is to find the peptide sequences to be phosphorylated by a target kinase, a recent advance in phosphoproteomics, kinase-interacting substrate screening (KISS) (Amano et al, 2015), facilitated the development of a novel ROCK FRET biosensor (Li et al, 2017).…”
Section: Future Perspectivesmentioning
confidence: 99%